2010
DOI: 10.1007/s10646-010-0481-4
|View full text |Cite
|
Sign up to set email alerts
|

Feathers as bioindicators of PCB exposure in clapper rails

Abstract: In this study we used feathers to biomonitor exposure to the polychlorinated biphenyl (PCB) Aroclor 1268 congener mixture in clapper rails (Rallus longirostris). This species has been used as an indicator species of environmental damage for the LCP superfund site located in Brunswick, GA, USA which is contaminated with Aroclor 1268, a congener mixture that has been used in limited amounts elsewhere and therefore can be used as a contaminant marker. The Aroclor 1268 congener mixture, including congener profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Following this, Van den Steen et al performed an experimental evaluation of the usefulness of feathers as a nondestructive biomonitor of PCBs in European Starlings ( Sturnus vulgaris ). Later still, several studies have evaluated the influence of external contamination on organic contaminant levels found in the feathers of several bird species as well as the correlations between levels in feathers and internal tissues. ,,,, Some studies have even reported on the concentrations of organic pollutants in feathers from museum collections. , …”
Section: Feathers and Organic Compoundsmentioning
confidence: 99%
“…Following this, Van den Steen et al performed an experimental evaluation of the usefulness of feathers as a nondestructive biomonitor of PCBs in European Starlings ( Sturnus vulgaris ). Later still, several studies have evaluated the influence of external contamination on organic contaminant levels found in the feathers of several bird species as well as the correlations between levels in feathers and internal tissues. ,,,, Some studies have even reported on the concentrations of organic pollutants in feathers from museum collections. , …”
Section: Feathers and Organic Compoundsmentioning
confidence: 99%
“…The specifi c PCB extractions for the feathers used in this study are described in detail by Summers et al (2010). In brief, the primary PCB congeners that compose Aroclor 1268 were quantifi ed in primary fl ight feathers.…”
Section: Methodsmentioning
confidence: 99%
“…Using these congeners and their respective ratios allows accurate identifi cation of Aroclor 1268 in biological media. An experiment using chicken feathers incubated in contaminated sediment was performed to determine if PCBs could be washed off the outside of the feather completely (Summers et al 2010). No PCBs were detected in these chicken feathers regardless of washing methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While feather plucking has been used to test for toxic chemicals in birds, feathers represent the concentration of pollutants during their formative stage only and may have significant contaminants on their outer surface. On the other hand, blood represents current circulating concentrations, and correlates much better with concentrations found in internal organs and tissues (Van den Steen et al 2007, Summers et al 2010). As both feather plucking and blood collection require a similar level of disturbance (i.e., capture), it seems prudent to simply take a blood sample in this and many other sampling scenarios given the additional scientific information likely to be obtained.…”
Section: The Case For Blood Collectionmentioning
confidence: 99%